Modeling and managing heterogeneous ride-sourcing platforms with government subsidies on electric vehicles. (September 2020) - Mo, Dong; Yu, Jingru; Chen, Xiqun Michael
Highlights: Formulateduopoly competition between two heterogeneous ride-sourcing platforms. Considerasset-lightandasset-heavy strategiesin the ride-sourcing market. Develop generalized waiting time cost function with increasing returns to scale. Deriveoptimal pricing strategies with adoption of EVs under competition equilibrium. Propose an optimization modelfor the determination of optimal subsidy strategies. Suggest government coordinate subsidies on the EVs purchase and charging stations. Abstract: This paper formulates duopoly competition between two non-cooperative heterogeneous ride-sourcing platforms considering the adoption of electric vehicles (EV) and government subsidies on EVs. One ride-sourcing platform adopts an EV asset-heavy strategy by undertaking EV depreciation costs, while the other ride-sourcing platform adopts an asset-light strategy by hiring drivers who own vehicles. The first-order conditions of each platform's pricingunder competitive equilibrium are derived based on a game-theoretical model that involves the stakeholders (i.e., riders, drivers, and ride-sourcing platforms). Based on the modeling framework ofduopoly competition between two heterogeneous ride-sourcing platforms, this paper proposes an optimization model with social welfare maximization for the determination of governmentsubsidy strategies. We conduct numerical illustrations to demonstrate how governmental subsidies on EV purchase and charging stations impact the endogenous variables in equilibrium (e.g., price for riders, wage for drivers, and market share for each platform) under different formulations of riders' waiting time cost function, which are increasing returns to scale. Also, a specialmodel with a fixed commission ratio is discussed. The results provide suggestions for decision-makers on how to allocate subsidy within the budget constraint.